Clinical risk management in obstetrics: eclampsia drills. Issue 2 (6th April 2004) - Thompson, S; Neal, S; Clark, V
Abstract : Problem: Infrequent presentation of patients with eclampsia, leading to staff inexperienced in the condition and untested emergency systems. Design: "Fire drill" programme using on-site simulation of patients with eclampsia. Setting: Tertiary referral obstetric unit. Key measures for improvement: Successful implementation of measures to optimise management of eclampsia. Strategies for change: Rapid activation of emergency team after one call, development and dissemination of evidence based protocol for eclampsia, strategically placed "eclampsia boxes, " individual staff feedback and education. Effects of change: Efficient and appropriate management of subsequent simulated patients. Lessons learnt: On-site simulation can identify and correct potential deficiencies in the care of patients with eclampsia.